2021
DOI: 10.1111/jwas.12863
|View full text |Cite
|
Sign up to set email alerts
|

The use of plant extracts to control tilapia reproduction: Current status and future perspectives

Abstract: Control of prolific reproduction is vital for a profitable tilapia aquaculture enterprise. All-male tilapia culture is a popular method used to control prolific breeding, because the male individuals grow faster than female and mixed-sex populations. Presently, most farmers use 17α-methyl testosterone (MT) to produce all-male tilapia individuals, although synthetic hormones are linked to human health and environmental risks. Recently, considerable attention has focused on plant-based products as alternatives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 168 publications
1
24
0
2
Order By: Relevance
“…It has been shown that some compounds found in plants could control reproduction in tilapia (12). Plants contain androgenic compounds, which have been reported to disrupt the reproductive cycle in fish (71)(72)(73)(74). Phytoandrogens such as testosterone, androstenedione and dehydroepiandrosterone have been shown to reverse the sex of fish (74), which can thus be used to reduce unwanted reproduction in tilapia.…”
Section: Use Of Plants To Improve Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that some compounds found in plants could control reproduction in tilapia (12). Plants contain androgenic compounds, which have been reported to disrupt the reproductive cycle in fish (71)(72)(73)(74). Phytoandrogens such as testosterone, androstenedione and dehydroepiandrosterone have been shown to reverse the sex of fish (74), which can thus be used to reduce unwanted reproduction in tilapia.…”
Section: Use Of Plants To Improve Reproductionmentioning
confidence: 99%
“…Plants contain androgenic compounds, which have been reported to disrupt the reproductive cycle in fish (71)(72)(73)(74). Phytoandrogens such as testosterone, androstenedione and dehydroepiandrosterone have been shown to reverse the sex of fish (74), which can thus be used to reduce unwanted reproduction in tilapia. Most of the phytochemicals (i.e., such as steroids, saponins, flavonoids, alkaloids, tannins) found in plants inhibit enzymes required for the production of sex hormones (74).…”
Section: Use Of Plants To Improve Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of analysis of variance showed that embryos soaked in pasak bumi extract had no effect on egg hatchability because the calculated F value < F table (< 0.05). The presence of pasak bumi extract added to each treatment did not affect the embryos to hatch because the pasak bumi extract used was not carcinogenic [16] other than that the pasak bumi extract given in each treatment was safe for the aquatic environment in the immersion container so that does not interfere with the growth and development of the embryo until it hatches [17].…”
Section: Egg Hatchabilitymentioning
confidence: 99%
“…The more concentration of pasak bumi extract may effect the higher percentage survival of fish for pasak bumi extract as natural ingredient is not harmful toward the water quality [23] in addition, the role of pasak bumi extract in betta fish is not only to increase testosterone production but also to help improve the immune system. immune system and fish growth performance [17].…”
Section: Life Survivalmentioning
confidence: 99%